Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1152/ajprenal.00002.2002
|View full text |Cite
|
Sign up to set email alerts
|

Arachidonic acid inhibits K channels in basolateral membrane of the thick ascending limb

Abstract: We have used the patch-clamp technique to study the effect of arachidonic acid (AA) on the basolateral K channels in the medullary thick ascending limb (mTAL) of rat kidney. An inwardly rectifying 50-pS K channel was identified in cell-attached and inside-out patches in the basolateral membrane of the mTAL. The channel open probability (Po) was 0.51 at the spontaneous cell membrane potential and decreased to 0.25 by 30 mV hyperpolarization. The addition of 5 M AA decreased channel activity, identified as NPo, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
20
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 27 publications
2
20
0
Order By: Relevance
“…Because the basolateral membrane potential determines the electrochemical gradient for Cl exit across the basolateral membrane, alteration of the cell membrane potential should affect the Cl exit across the basolateral membrane and indirectly the activity of the Na/Cl/K cotransporter in the apical membrane. Several types of basolateral K channels have been identified with patch-clamp experiments (8,19). We and others have confirmed that a 50 pS inwardly rectifying K channel was highly active in the basolateral membrane.…”
supporting
confidence: 61%
“…Because the basolateral membrane potential determines the electrochemical gradient for Cl exit across the basolateral membrane, alteration of the cell membrane potential should affect the Cl exit across the basolateral membrane and indirectly the activity of the Na/Cl/K cotransporter in the apical membrane. Several types of basolateral K channels have been identified with patch-clamp experiments (8,19). We and others have confirmed that a 50 pS inwardly rectifying K channel was highly active in the basolateral membrane.…”
supporting
confidence: 61%
“…The observations that activating mutations of the human CaSR gene can cause a Bartter's-like phenotype further support this concept (Watanabe et al 2002). Other studies have demonstrated that P-450-dependent metabolites of arachidonic acid most likely 20-HETE , as well as Mg 2+ and spermine, which are known as potent calcimimetics, and low pHi inhibit basolateral membrane 50-pS K channels in TAL (Gu et al 2002;Paulais et al 2002) This basolateral K + conductance maintains driving force for the basolateral diffusion of Cl -and participates in the basolateral efflux of K + ions to partially compensate for the influx of K + ions associated with Na + -K + -ATPase activity. We found that CaSR-related alkalinization was still present under ambient Na + -free conditions, but was completely inhibited under apical K + -free conditions and by applications of HKa blockers Sch-28080 and ouabain.…”
Section: Discussionmentioning
confidence: 74%
“…However, the authors have been unable to ascertain to which specific K ϩ channel gene families these K ϩ channels belong. Unclassified channels are reported in the basolateral membrane of PT cells (7, 32, 33, 51-53, 62, 63, 97, 111, 125), TAL cells (24,39,40), DCT cells (123), and CNT/CD cells (36,(47)(48)(49)82).…”
Section: Kcnj Gene Family Members In the Nephronmentioning
confidence: 99%